Medical student and trainee doctor views on the 'good' doctor: Deriving implications for training from a Q-methods study. (2nd September 2022) - Coventry, Jennifer; Hampton, Jennifer May; Muddiman, Esther; Bullock, Alison
Abstract: Purpose: In context of changing patient demographics, this study explores what doctors and medical students believe being a 'good' doctor means and identifies implications for training. Method: Using Q-methodology, a purposive sample of 58 UK medical students and trainees sorted 40 responses to the prompt 'Being a "good" doctor means….' Participants explained their array choices in a post-sort questionnaire. Factor-groups, consensus and distinguishing statements were identified using Principal Components Analysis in R. Results: Three factor-groups best described shared and divergent perspectives, accounting for 61.64% of variance. The largest, 'patient-centred generalist' group valued patient wellbeing and empowerment, compassion and complex needs. They prioritised knowledge breadth and understanding other specialties. The 'efficient working doctors' group valued good work-life balance, pay and did not seek challenge. Some believed these made a stressful career sustainable. The 'specialist' group valued skills mastery, expertise, depth of knowledge and leadership. Participant-groups were distributed across these factor-groups, all agreeing early specialisation should be avoided. Conclusions: The largest factor-group's perceptions of holistic, patient-centred care align with Royal Colleges' curricula adaptions to equip doctors with generalist skills to manage multi-morbid patients. However, curriculum designers should acknowledge implications of generalist approaches for doctors' formulation of professional identities.